Complement component c1q and anti-c1q antibodies in theory and in clinical practice - Potlukova, E; Kralikova, P (Scandinavian journal of immunology, 2008)
The complement system is a major part of the innate immunity. The first component of the classical pathway of complement activation, C1q, plays a crucial role in the clearance of immune complexes and apoptotic bodies from the organism. Autoantibodies against C1q (anti-C1q) have been found in a number of autoimmune and infectious diseases. They have been best described in patients with systemic lupus erythematosus, where they are thought to play a pathogenic role in lupus nephritis (LN). Their high negative predictive value for the occurrence of active proliferative LN, as well as their possible ability to indicate a renal flare as soon as 6 months in advance, have rendered anti-C1q antibodies a novel non-invasive tool in the detection of active LN.
Keywords: Animals; apoptóza; přirozená imunita; systémový lupus erythematodes; Complement Pathway, Classical; biologické markery; Complement C1q; Biomarkers; Apoptosis; Antigen-Antibody Complex; lidé; Lupus Erythematosus, Systemic; Humans; imunokomplex; Lupus Nephritis; progrese nemoci; nefritida při lupus erythematodes; klasická dráha komplementu; Autoantibodies; Disease Progression; Immunity, Innate; komplement C1q; zvířata; autoprotilátky